HOW SHOULD WE SUFFER? MEDITATING ON CHRISTIAN RESPONSES TO THE PROBLEM OF SUFFERING - Dickinson, Colby (Estudos teológicos, 2020)
Despite the irreducible non-equivalence of individual experiences of suffering, there is a solidarity possible among sufferers especially during times of collective crisis. This essay focuses on the suffering of the disciple Peter in order to formulate a model for suffering that resonates deeply with other, more recent accounts. Peter’s suffering is linked with Bryan Stevenson’s Just Mercy, as well as the work of certain German political theologians, in order to show how it is our human inability to adequately respond to suffering that gives us the existential vulnerability we need in order to stand in solidarity with others who suffer too—the primal element of Christian love. At a precarious time when so many feel a vulnerability perhaps never felt before, such vulnerability potentially transforms us into more responsible social agents and political actors.